SEASONAL MONITORING OF DESNA RIVER WATER DURING 2024 - Zhydenko Алла; Papernyk Вікторія (Biota. Human. Technology, 2025)
Purpose of work: to analyse the hydrochemical indicators of the Desna River water during 2024, to show the impact of individual pollutants on human health. Methodology: In accordance with the updated orders of the Ministry of Environment dated January 9, 2024 No. 37 “On Approval of the State Water Monitoring Program” and the State Water Agency dated January 12, 2024 No. 7 “On the Implementation of the Procedure for State Water Monitoring”, the Desna Basin Water Resources Department carried out diagnostic and operational monitoring of surface water bodies of the Upper Dnieper and Desna River sub-basins during 2024. The results of monitoring observations of the Desna River were used as initial information for calculations and preparation of tables and graphs. Based on the analysis of these data, conclusions were made. Scientific novelty: Analysis of the obtained data showed a relationship between changes in the concentration of total iron, manganese and dissolved organic substances (easily oxidizable, which were determined by the indicator CODМn). For all these indicators, exceeding the TLV for fishery reservoirs was recorded in all seasons. The simultaneous increase in CODМn in March, June and August 2024 was largely due to the presence of organic substances of a carbohydrate, rather than protein-like nature, since changes in the concentrations of ammonium nitrogen and its metabolites were not significant during this period. Conclusions: 1) seasonal changes in the concentration of water pollutants in the Desna River during 2024 were influenced by abiotic, anthropogenic factors and military actions (pollution of the Seim River by the discharge of unknown waste from Russian territory); 2) the concentration of dry residue, phosphate ions, nitrate and nitrite nitrogen in the water of the Desna River during 2024 fluctuated within normal limits; 3) the concentration of ammonium nitrogen (except in May) exceeded the TLV for water bodies intended for fishery purposes. Its highest amount was observed in August, September and November (as a result of pollution of the Seim River); 4) in all seasons of 2024, the average values of CODMn, total iron (Fe2+ and Fe3+), and manganese consistently exceeded the TLV for fishery reservoirs; 5) according to the ecological classification of the quality of surface waters of land and estuaries according to trophozo-saprobiological criteria during 2024, the water of the Desna River, according to the averaged BOD5 values, belongs to classes III and IV (“satisfactory” and “bad”).